Analyzing the Interplay: Micro, Small and Medium Enterprises (MSMEs) and Foreign Direct Investment (FDI) Impact on Indonesian Export - Riesty Yunda Sari; Dedy Yuliawan; Ukhti Ciptawaty; Neli Aida; Heru Wahyudi; Arivina Ratih Y.T (Journal on Education, 2024)
Indonesia, as a country with an open economic system, is inherently intertwined with international trade activities encompassing both exports and imports. This study aims to explore and quantify the influence of Micro, Small, and Medium Enterprises (MSMEs) and Foreign Direct Investment (FDI) on Indonesia's export sector. Employing a quantitative approach, the research utilizes time series data spanning from 2008 to 2022, sourced from the Central Statistics Agency (BPS). Utilizing the multiple linear regression method, the research analyzes the intricate relationships between MSMEs, FDI, and export dynamics. The comprehensive dataset enables a meticulous examination of the roles these factors play in shaping Indonesia's position in the global market. This research holds significant implications for policymakers, businesses, and stakeholders involved in fortifying Indonesia's global market presence. The insights gleaned from this study contribute to a nuanced understanding of the economic dynamics, offering a foundation for sustainable growth strategies. Following the analysis of the data and subsequent discussion, it can be inferred that the FDI variable positively impacts